The Role of The Central Bank on Economic Growth (Study Case: Indonesia) - Asyadia Haq Zahra Wijaya; Munawar Ismail; Dwi Budi Santosa (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2023)
Over the past decade, Indonesia has had a relatively low economic growth rate compared to several countries in Southeast Asia. The role of the central bank is one of the instruments that need to be considered to encourage economic growth in Indonesia. As a result, examine how the central bank influence economic growth through controlling inflation, current rate, and interest rate as a policy is the purpose of this study.  Interest rates and exchange rates are shown to be significantly corelated to the economic growth in both the short- and long-term in this study using the ARDL approach. This discovered there is no significantly correlation between inflation and economic growth over the long and short terms. The analysis demonstrates the many steps the central bank has taken to promote economic growth.